I, a Ngwazla - Elie, Wouleo Kazla (Journal of Anthropological Films, 2022)
“I, a Ngwazala” is a cross-examination of the Ngwazla caste of Mafa society. It gives valuable insight into the lives of blacksmiths and how their culture is currently exposed to rapid transformation. This documentary presents Zayadai our key character who although trained as a blacksmith by his father, was able to study. And on the death of his father, he abandoned his studies to practice the profession of blacksmith, a profession passed down from father to son. Helped by his three young brothers, he exercises his art in order to meet the demand of the inhabitants of Djinglia Kongoche and by extension to meet the needs of his wife, his mother and his 11 brothers. Thus it gives access to important transformation processes in the Mafa society. Although the old strict separation of the Ngwazla is still present, but the increased contacts with the outside world and the influences of locally established institutions, such as the modern school system, Christian mission and Islam, are revealing new identities of Ngwazla . The Ngwazla are proud of their identity and are trying to reshape it in line with the rapid societal transformation underway.